Ecosystem Assessment for Sustainable Management : A Case Study of Coringa Mangroves, Andhra Pradesh, India - Ramesh, Devaraj Asir; Muthukrishnan, L.; Balamurugan, S.; Karthi, N.; Dhivya, S. (Arthshastra Indian Journal of Economics & Research, 2021)
Coastal ecosystems contribute to the economy by providing various goods and services. Ignorance about the economic importance of these goods and services leads to overexploitation and depletion of ecosystems in the long run, thereby affecting sustainability. This study attempted to estimate the economic value of goods and services of Coringa mangroves, Andhra Pradesh, by adopting the System of Environmental Economic Accounting – Experimental Ecosystem Accounting framework. The framework guides to assess the extent and condition of ecosystem assets and estimates the ecosystem service flows in physical and monetary terms for better decision making on sustainable management. The goods and services identified in Coringa mangroves were classified as provisioning, regulatory, and cultural services as specified in the framework. The study found that Coringa mangroves produce 11 goods and services with a total economic value of ₹549.6 crores per year. A meta-analysis study was conducted to compare the benefits of Coringa mangroves with other mangrove sites of the world. The study revealed that honey and medicinal benefits, with an estimated worth of ₹1.92 crores per year, have remained unutilized in Coringa. To exploit the unutilized potentials of Coringa mangroves in a sustainable way, this study recommends capacity-building activities that will help link the environment with economics and seed investments.